2004
DOI: 10.1017/s0140525x04000196
|View full text |Cite
|
Sign up to set email alerts
|

An evolutionary theory of schizophrenia: Cortical connectivity, metarepresentation, and the social brain

Abstract: Schizophrenia is a worldwide, prevalent disorder with a multifactorial but highly genetic aetiology. A constant prevalence rate in the face of reduced fecundity has caused some to argue that an evolutionary advantage exists in unaffected relatives. Here, I critique this adaptationist approach, and review – and find wanting – Crow's “speciation” hypothesis. In keeping with available biological and psychological evidence, I propose an alternative theory of the origins of this disorder. Schizophrenia is a disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
107
1
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(120 citation statements)
references
References 509 publications
(470 reference statements)
4
107
1
4
Order By: Relevance
“…the faster a species lived, the faster it would die. But although life span is not unrelated to metabolism (Economos, 1981), the rate of living theory remains controversial (Burns, 2004) and is generally discounted (Lints, 1989). …”
Section: Model Speciesmentioning
confidence: 99%
“…the faster a species lived, the faster it would die. But although life span is not unrelated to metabolism (Economos, 1981), the rate of living theory remains controversial (Burns, 2004) and is generally discounted (Lints, 1989). …”
Section: Model Speciesmentioning
confidence: 99%
“…Recently, it has been suggested that consciousness depends on the brain's ability to integrate information among different thalamo-cortical areas [8]. Disruption in cortical connectivity has been also implicated in a number of disorders and pathologies, such as schizophrenia [3], autism [21], brain trauma [23] and so on. As a result there is a shift of research attention from localised brain function to network organization and dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Since some schizophrenic disorders are likely to be accounted for by explanations of an evolutionary nature, at least as far as language [10], reasoning [8,9], and social behavior [5] are concerned, we can expect that the study of such pathological interactions will tell us something about the rationality of the cognitive processes listed above. Indeed, the manifestation of the disorder during interactions and the need to maintain the link cause the schizophrenic interlocutor to adopt a compensatory management strategy.…”
Section: Discussionmentioning
confidence: 99%